2020
DOI: 10.21203/rs.3.rs-54114/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health professional and patient perspectives of factors associated with potentially avoidable hospitalisations in a rural Australian setting: a qualitative study

Abstract: Background Potentially avoidable hospitalisations are a proxy measure of effective primary care at a population level. Hospitalisations for the chronic health conditions of diabetes, congestive cardiac failure and chronic obstructive pulmonary disease account for half of the potentially avoidable hospitalisations for chronic diseases. These hospitalisations are higher in rural areas and socioeconomically disadvantaged areas. Scarce qualitative research has focussed on the identification of factors associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, little research captured the patient’s perspective on the leading causes of ACSC hospitalizations [ 1 ] and what could have been done to avoid it. One study in Australia conducted semi-structured interviews with patients and health professionals to identify factors associated with potentially avoidable hospitalizations in a rural context [ 18 ]. Authors identified complex and interrelated factors associated with potentially avoidable hospitalizations, classified into five themes: General Practitioner involvement, individual patient factors, the influence of the rural locality, medication awareness, and health service access.…”
Section: Introductionmentioning
confidence: 99%
“…However, little research captured the patient’s perspective on the leading causes of ACSC hospitalizations [ 1 ] and what could have been done to avoid it. One study in Australia conducted semi-structured interviews with patients and health professionals to identify factors associated with potentially avoidable hospitalizations in a rural context [ 18 ]. Authors identified complex and interrelated factors associated with potentially avoidable hospitalizations, classified into five themes: General Practitioner involvement, individual patient factors, the influence of the rural locality, medication awareness, and health service access.…”
Section: Introductionmentioning
confidence: 99%